2017
DOI: 10.1016/j.bbadis.2017.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Reelin protects from colon pathology by maintaining the intestinal barrier integrity and repressing tumorigenic genes

Abstract: We previously reported that reelin, an extracellular matrix protein first known for its key role in neuronal migration, reduces the susceptibility to dextran sulphate sodium (DSS)-colitis. The aim of the current study was to determine whether reelin protects from colorectal cancer and how reelin defends from colon pathology. In the colon of wild-type and of mice lacking reelin (reeler mice) we have analysed the: i) epithelium cell renewal processes, ii) morphology, iii) Sox9, Cdx2, Smad5, Cyclin D1, IL-6 and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…However, there has been no study on the correlation between GDNF methylation and the prognosis of colon cancer. RELN has been reported to play a critical role in maintaining epithelial cell ho-meostasis and protecting the colon from pathological processes[44]. Furthermore, RELN is epigenetically regulated by methylation in gastric cancer[45], pancreatic cancer[46], hepatocellular cancer[47], and myeloma[48].…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been no study on the correlation between GDNF methylation and the prognosis of colon cancer. RELN has been reported to play a critical role in maintaining epithelial cell ho-meostasis and protecting the colon from pathological processes[44]. Furthermore, RELN is epigenetically regulated by methylation in gastric cancer[45], pancreatic cancer[46], hepatocellular cancer[47], and myeloma[48].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that reelin absence increases colitis severity and colon tumorigenesis in mice [ 19 , 20 ] and that reelin was upregulated in the colon of a mouse model of acute colitis and downregulated in human colon adenocarcinoma [ 19 , 21 ]. These reelin changes were the opposite of those in DNMT-1 expression and activity, which, via the hypomethylation of the reelin promoter in acute colitis and hypermethylation in colon adenocarcinoma, increases or represses reelin expression, respectively [ 19 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mutual interactions between the epithelium and the underlying basement membrane regulate proliferation, migration, differentiation, apoptosis, morphogenesis, tissue repair, inflammation, and immune response [31]. Many receptors have been identified for cellextracellular matrix molecules in intestinal epithelial cells, many of which are integrins [32]. However, the nature of cell-basement membrane interactions and their intracellular processing is largely undefined.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that Reelin deficiency is associated with bipolar disorder and major depression, autism, epilepsy, and schizophrenia [27][28][29][30]. There are also studies suggesting that Reelin may play a role in inflammatory bowel diseases [31][32][33]. Additionally, studies show its function in crypto-villus homeostasis and that Reelin regulation plays a protective role against diseases such as acute colitis [31,34].…”
Section: Introductionmentioning
confidence: 99%